Law Enforcement Of The Stockholm Declaration Principles In Relation To Forest And Land Fires In Indonesia - Indien Winarwat (Technium Social Sciences Journal, 2023)
The frequent forest fires in Indonesia are of important concern for ASEAN countries since Indonesia is considered the biggest contributor to smoke-haze pollution. Land and forest fires in Indonesia contribute to exporting haze to Malaysia and Singapore, causing the two countries to urge Indonesia to immediately address the issue of forest fire since the resulting smoke haze is terribly disturbing and dangerous for the people of both countries. Indonesia is one of the developing countries currently in the international spotlight due to the severe damage to its tropical forests annually. Land and forest fires in Indonesia constitute a transnational environmental pollution, creating a thick smoke haze to disrupt the continuity of life and economic activities in most of the region of ASEAN countries. The impacts of the smoke haze caused by forest and land fires are immense, requiring the Indonesian Government to take a firm stand by immediately making regulations to ensnare forest and land burners to cause a deterrent effect not to do the foregoing again. The present paper addresses law enforcement arrangements for land and forest fires in Indonesia and the harmony of the Stockholm Declaration principles with law enforcement arrangements for forest and land burners. The present study is analytical descriptive using the normative juridical approach. It describes the phenomenon and analyzes the legal issues of law enforcement arrangements for land and forest fires. Results show that law enforcement by the Government of Indonesia is regulated by Law Number 41 of 1999 concerning Forestry, Law Number 18 of 2004 concerning Plantations and Law Number 32 of 2009 concerning Environmental Protection and Management. Each of these laws includes provisions on criminal sanctions and fines for forest and land burners. Law enforcement of the Stockholm Declaration principles for forest and land fires is accommodated in Articles 49 and 50 of Law on Forestry.